Study of Religious Philosophy on Tapa Brata (Javanese Asceticism Practice) to Overcome the Social Anxiety During COVID-19 Pandemic Era - Suryosumunar, John Abraham Ziswan (Prodi Aqidah dan Filsafat Islam, Fakultas Ushuluddin, Universitas Islam Negeri Sunan Kudus, 2021)
The COVID-19 pandemic, which is global disaster, has an impact on all aspects of human life. Indonesia is one of the countries that has a high rate of COVID-19 transmission, this has an effect on various policies in suppressing transmission rates by limiting social mobility. In the midst of this pandemic, people are faced with uncertain conditions that result in levels boredom, fear and even public anxiety increased. The author is interested in exploring the realities of the COVID-19 pandemic by seeing that there is a relationship between public anxiety during the COVID-19 pandemic and awareness of the need for spirituality in facing the various changes that have occurred. Using the philosophical hermeneutic method, this qualitative research was conducted by trying to discuss one of the spiritual practices of Javanese society, namely Tapa Brata, and to relate it to public anxiety that occurred during the COVID-19 pandemic. The results of the discussion carried out are: (1) anxiety in the people during the pandemic period is caused by awareness of an uncertain and constantly changing reality. (2) Tapa brata is the mental practice of forming a self that is calm and wise in accepting all changes. (3) Tapa brata is an inner practice that is personal and can overcome public anxiety during a pandemic and has a physiological effect in increasing immunity during the Covid-19 pandemic.